A Patient With a Protuberant Fibro-Osseous Lesion of the Temporal Bone. Issue 5 (July 2019) - Maroun, Christopher A.; Khalifeh, Ibrahim; Faddoul, Daniel S.; Zaytoun, George; Moukarbel, Roger V.
Abstract : Abstract: Protuberant fibro-osseous lesion of the temporal bone, otherwise known as "Bullough's lesion", is a rare, benign exophytic fibro-osseous tumor. In this brief report, we present a case of a 61-year-old woman with a history of a right-sided skull mass that had been increasing in size for approximately 6 years before presentation. Clinical, radiological and histological features are examined and discussed. We achieved excellent results with surgical resection, with no evidence of recurrence.